The identity of Hypolepis robusta, as a new synonym of Hypolepis alpina (Dennstaedtiaceae), based on morphology and DNA barcoding and the new distribution - Morigengaowa; Jun-Jie Luo; Ralf Knapp; Hong-Jin Wei; Bao-Dong Liu; Yue-Hong Yan; Hui Shang (PhytoKeys, 2018)
Based on field observations and examinations of herbarium specimens (including type material), consulting the original literature and molecular phylogenetic analysis of the rbcL and trnL-F sequences, it is concluded that Hypolepis robusta is conspecific with Hypolepis alpina and is here formally treated as a synonym of it. Additionally H. alpina is reported with new distribution records in Guangdong, Guangxi and the Hainan Island of China, respectively.